Struktur Stomata Pada Familia Poaceae Di Desa Kota Bumi Kecamatan Tanjung Lubuk Kabupaten OKI - Dewi Rosanti; Trimin Kartika; Miftahul Jannah (Indobiosains, 2023)
Research on Stomata Structure in the Poaceae Family in Kota Bumi Village, Tanjung Lubuk District, Ogan Komering Ilir Regency, was carried out from April to May 2022. The purpose of the study was to examine the stomata structure on the adaxial (top) and abaxial (bottom) leaves of the Poaceae family. This study uses a descriptive survey method by going directly to the research location exploring the area of ​​Kota Bumi Village, Tanjung Lubuk District, Ogan Komering Ilir Regency. Sampling was done by direct observation observing the stomata structure of the adaxial (top) and abaxial (bottom) leaves of rice plants (Oryza sativa.), corn (Zea mays), reeds (Imperata cylindrica), sugarcane (Saccharum officinarum) and lemongrass ( Cymbopogon citratus). The results of the study found that 5 species had stomata located on the surface of the leaf Adaxia (top) and Abaxial (bottom) leaf. Amphistomatic type of stomatal spread. The shape of each guard cell is in the shape of a dumbbell. The number of neighboring cells is 2 neighboring cells. Both have the type of Stomata Graminae, the shape of the epidermal cells is elongated, grooved, rounded, parallel elongated, and grooved